Light Thresholds to Prevent Dredging Impacts on the Great Barrier Reef Seagrass, Zostera muelleri ssp. capricorni - Chartrand, Kathryn M.; Bryant, Catherine V.; Carter, Alex B.; Ralph, Peter J.; Rasheed, Michael A. (Frontiers in Marine Science, 2016)
Coastal seagrass habitats are at risk from a range of anthropogenic activities that modify the natural light environment, including dredging activities associated with coastal and port developments. On Australia’s east coast, the tropical seagrass Zostera muelleri ssp. capricorni dominates intertidal mudbanks in sheltered embayments which are also preferred locations for harbours and port facilities. Dredging to establish and maintain shipping channels in these areas can degrade water quality and diminish light conditions that are required for seagrass growth. Based on this potential conflict, we simulated in-situ light attenuation events to measure effects on Z. muelleri ssp. capricorni condition. Semi-annual in situ shading studies conducted over three years were used to quantify the impact of prolonged light reduction on seagrass morphometrics (biomass, percent cover and shoot density). Experimental manipulations were complimented with an assessment of 46 months of light history and concurrent natural seagrass change at the study site in Gladstone Harbour. There was a clear light-dependent effect on seagrass morphometrics during seagrass growing seasons, but no effect during senescent periods. Significant seagrass declines occurred between four and eight weeks after shading during the growing seasons with light maintained in the range of 4 - 5 mol photons m-2 d-1. Sensitivity to shading declined when applied in two-week intervals (fortnightly) rather than continuous over the same period. Field observations were correlated to manipulative experiments to derive an applied threshold of 6 mol photons m-2 d-1 which formed the basis of a reactive light-based management strategy which has been successfully implemented to ensure positive ecological outcomes for seagrass during a large-scale dredging program.